THE EBB AND FLOW OF SCIENCE AND RELIGION RELATIONSHIP IN AFFECTING HUMAN LIFE - Ahida, Ridha (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2020)
This research aimed at discovering the root of the problem of the relation between science and religion, identifying how conflict and collaboration between science and religion answer the challenges that human life pose and describing how religion in the future synergize with the advancement of science. This research emphasizes on the need to delve on the issues related to science and religion since the advancement of science often contradicts with some aspect of the Holy Book as well as the assumption that science rattles someone’s faith. Religion is also often regarded as something that hinders the development of science and people who participate in science development are often considered an infidel. There is a skeptical nuance that arose regarding the relationship between science and religion. Thus, it is of utmost importance to investigate on the ebb and flow of science and religion relation in affecting human life. This research employed methodology of philosophy, especially science philosophy in the form of justification and history of science. This research indicated that science and religion are both collaborating and confronting. Religion is used to make meaning of life and science is used to make life easier. Keywords: Religiosity, Rationality, Confrontation, and Collaboration